PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PRESTASI BELAJAR MAHASISWA - Widyasari, Riztika; Santi, Triana Kartika (Nusantara Hasana Berdikari, 2022)
One of the factors that lead to low student achievement is that the lecturers are less precise in using learning media. The purpose of this classroom action research is to apply the use of interactive learning media to improve student achievement in the Learner Development course. The design used by Kemmis and Mc-Taggart's action research model is a spiral. The final results of the second cycle obtained in a good category for improving learning achievement have reached a value with a good category of 84%, this exceeds the expected target of 75%. This indicates that the use of interactive learning media that presents learning content such as text, graphics, images, photos, integrated audio, video and animation are very suitable to improve student achievement in the Learner Development course.